Improvement of DSOGI PLL Synchronization Algorithm with Filter on Three-Phase Grid-connected Photovoltaic System (Jurnal Elektronika dan Telekomunikasi, 2018)
Synchronous Reference Frame Phase Locked Loop (SRF PLL) has been widely used for synchronization three-phase grid-connected photovoltaic (PV) system. On the grid fault, SRF PLL distorted by negative sequence component and grid harmonic that caused an error in estimating parameter because of ripple and oscillation. This work combined SRF PLL with Dual Second Order Generalized Integrator (DSOGI) and filter to minimize ripple and minimize oscillation in the phase estimation and frequency estimation. DSOGI was used for filtering and obtaining the 90o shifted versions from the vαβ signals. These signals (vαβ) were generated from three phase grid voltage signal using Clarke transform. The vαβ signal was the inputs to the positive-sequence calculator (PSC). The positive-sequence vαβ was transformed to the dq synchronous reference frame and became an input to SRF-PLL to create the estimation frequency. This estimation frequency from SRF PLL was filtered by the low-pass filter to decrease grid harmonic. Moreover, the output of low-pass filter was a frequency adaptive. The performance of DSOGI PLL with filter is compared with DSOGI PLL, SRF PLL, and IEEE standard 1547(TM)-2003. The improvement of DSOGI PLL with filter gave better performances than DSOGI PLL and SRF PLLbecause it minimized ripples and oscillations in the phase and frequency estimations.